Dandiacal Conversation in Oscar Wilde’s Comedies of Manners: Conventions, Conversions and Reconfigurations of Phallogocentrism - Gilbert Pham-Thanh (Cahiers Victoriens et Edouardiens)
Wilde’s comedies of manners stage dandies enjoying relative freedom in the parlours, ballrooms and reception halls where the scenes usually take place. From a marginal position, the characters progressively conquer centerstage. They are not only accepted but sought after, as ultra-refined figures of conventional gentlemanliness and masters of ceremonies of sorts.Their presentability is matched by their power to convince whoever engages in controversies with them. Their strong reliance on rhetoric ensures their supremacy in polite conversation, even if their intellectual and cultural edge does a lot to secure their domination. What is more, their mastery of codes and norms enables them to destabilize the semantics of the age, a gesture which can be equated to a reconfiguration of Victorian patriarchy and even a dismissal of Victorian grand narratives.